Combined analysis of the endophytic fungi and volatile oil content of different Aquilaria sinensis germplasms revealed the correlations between endophytic fungal abundances and agarwood production - Yuyin Zhang; Zixiao Jiang; Hua Dou; Chenlu Fan; Jianhe Wei; Jianhe Wei; Jianhe Wei; Xuyu Chen (Frontiers in Plant Science)
IntroductionAgarwood, a prized aromatic resin from Aquilaria sinensis, is formed as a defensive response to injury or fungal infection. However, the factors influencing its chemical composition remain poorly understood. This study aimed to explore the relationship between endophytic fungal communities and volatile oil content in ordinary-type and Qinan-type A. sinensis.MethodsUsing high-throughput sequencing, we analyzed the fungal composition in both the healthy wood and agarwood layers of different A. sinensis germplasms. Additionally, gas chromatography-mass spectrometry (GC-MS) was employed to quantify the volatile oil content.ResultsThe results revealed that the fungal community composition in the agarwood layer differed between the two types of A. sinensis, with Fusarium, Hermatomyces, and Rhinocladiella linked to sesquiterpene production (r>0.8, p<0.01), while Microidium, Cladosporium, and Cephalotrichum were associated with chromone levels (r>0.8, p<0.01). Furthermore, the volatile oil content in Qinan-type agarwood was significantly higher than that in ordinary-type agarwood, with distinct chemical profiles observed in each germplasm.DiscussionThese findings provide critical insights into the role of endophytic fungi in shaping agarwood's chemical composition and have practical implications for enhancing agarwood production in the industry. Consequently, this research has significant implications for the agarwood industry, as it enhances our understanding of how fungi influence resin quality and paves the way for improving the efficiency of agarwood induction, ultimately leading to higher-quality and more sustainable production.